Retrograde endoscopic cholangiopancreatography: Analysis of the epidemiological profile and complications - Campos, Rayssa Kethlyn Alves de; Silva, Izabelle Louise de Almeida; Alécio, Camila Cínthia Araújo; Costa , Daniel Pacheco da; Amaral, Carlos Henrique Barros; Batista, Leandro Valério Costa; Melo, Tiago Torres; Lacet, Celina Maria Costa (Seven Editora, 2023)
Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) is an important diagnostic and therapeutic tool used in the management of hepatobiliary and pancreatic diseases. Post-ERCP pancreatitis is the most common complication of this procedure. We evaluated the results of patient procedures found at ERCP in a reference service of the SUS, determining a success rate, epidemiological profile and frequency of complications. Methods: Retrospective and cross-sectional study carried out from August 2019 to December 2020, with a final sample of 217 patients. Information was collected from the database of the Santa Casa de Maceió Endoscopy Service, using a semi-structured questionnaire containing age, gender and data regarding: indication of the ERCP procedure, success rate, in addition to complications. The description of the data obtained was presented using descriptive statistics. Results: We observed a predominance of females (70.5%), with a mean age of 53.9 years. All therapeutic procedures and choledocholithiasis represent the main indication (76.4%). The most common procedures were: biliary cannulation for stone removal (62.2%), passage of biliary stent (19.8%) and removal of biliary stent (10.5%). The procedure success rate was 92.6%, complications occurred in 6.45%, the main one being acute pancreatitis in 3.7%. Conclusion: The study concluded that the main indication for performing ERCP was biliary obstruction by calculus. The observed success rate of the procedure was 92.6%. Complications after ERCP were infrequent (6.45%), with the highest frequency being acute pancreatitis, with an incidence of 3.7%. DOI:https://doi.org/10.56238/sevened2023.006-009